O corte na educação e a política da morte: humor, cinismo e resistência nas charges de Duke - Silva, Renato Hollanda (2021)
It is problematized in this master's research, the discursive functioning of charges formulated based on the controversial decisions and statements of the Bolsonaro government on the subject of “contingency” of funds for higher education. In view of a corpus built from clippings of charges by Duke, published in the newspaper O Tempo, the objective is to understand processes of producing meanings of resistance to Bolsonarist discourse, which implies examining the different subject-positions that confront and face in charges, considered verb-visual formulations. Anchored in the assumptions of Discourse Analysis, in the wake of Pêcheux and Orlandi, concepts such as discursive memory, interdiscourse, event, interpellation/identification, subject-position etc., are articulated, which support the analyzes carried out in the mix between description and interpretation and they aim to problematize the different ideological positions underlying the political proposals of higher education for Brazilian society. The analyzes reveal the discursive functioning of the charges, indicating a discursive process that affirms a critical position when articulating effects of humor and resistance, resulting from a practice affiliated to the old cynicism (kynismos), whose operating mode puts irony and humor on the scene. From them it is possible to recognize the necropolitics or politics of death that underlies Bolsonarist discourses and practices, questioning their effects and social implications. (This work was carried out with the support of the Coordination for the Improvement of Higher Education Personnel – Brazil (CAPES) – Financing Code 001). Keywords: Discourse Analysis; charges; humor; resistance; kynisms-cynicism.